PERKEMBANGAN KEBIJAKAN NILAI TUKAR RUPIAH DAN PERTUMBUHAN EKONOMI INDONESIA - Fitriyani Fitriyani; Diana Sapha; Cut Zakia Rizki; Nur Aidar; Ferayanti Ferayanti; Muhammad Ilhamsyah Siregar; Amsal Irmalis (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2019)
This study aims to analyze the development of exchange rate system, inflation and economic growth policies in Indonesia. The model used is a descriptive analysis model by dividing 3 exchange rate regimes from 1978 to 2018. The data used is annual data sourced from the world bank, the federal reserve economic data, and Bank Indonesia. The results showed that the exchange rate system in Indonesia is fluctuated throughout the year. This has an impact on economic growth rate and inflation which is also unstable. Therefore, Bank Indonesia must stabilize the rupiah exchange rate. For further research, it is also advisable to further analyze how the 3 periods of the exchange rate regimes work effectively in transmitting monetary policy through the exchange rate channel to macro variables.Key Words: Exchange rate, growth rate, inflation